Isolated Hydatid Cyst of Kidney: A Case Report (Faridpur Medical College Journal, 2016)
Hydatid disease, caused by Echinococcus granulosus is still endemic in certain parts of world but not a common disease in our country. Hydatid cysts mainly involve the liver and lungs but any other organ can potentially be involved. Renal hydatid cyst is uncommon and represents 2-4% of hydatid cyst in human. We report a case of isolated hydatid cyst of right kidney in our surgical care. A 36 years old lady was admitted under our care with gradually increasing lump and mild pain in right lumbar region for 6 months. Ultrasonography revealed a diagnosis of hydatid cyst. IVU showed smooth filling defect in right kidney which displaced pelvicaliceal system. Serological tests were not done due to unavailability. The patient was operated on and endocystectomy, deroofing and marsupialization were done. Hydatid cyst was confirmed by histopathological examination. Albendazole was started 2 weeks before operation and continued postoperatively for 1 month. The patient was discharged on 8th postoperative day and was closely followed up for 3 years without any further development of hydatid cyst in any organ.Faridpur Med. Coll. J. Jan 2015;10(1): 40-43